Reseña de Pizarro Pedraza, Andrea (ed.) (2018): Linguistics Taboo Revisited: Novel Insights from Cognitive Perspectives - Gómez Díaz, Sara (Pragmalingüística, 2020)
Se trata de una reseña de Pizarro Pedraza, Andrea (ed.) (2018): Linguistics Taboo Revisited: Novel Insights from Cognitive Perspectives.